Physical Activity Patterns in a Representative Sample of Adolescents from the Largest City in Latin America: A Cross-Sectional Study in Sao Paulo - De Moraes-Ferrari, G (NLM (Medline), 2020)
OBJECTIVES: We examined the patterns of total and domain-specific physical activity (PA) by sex, socioeconomic status and maternal education level in adolescents from Sao Paulo city, Brazil. DESIGN: Cross-sectional study. PARTICIPANTS: We included a representative sample of 2682 (52.2% boys) adolescents aged 14-15 years from public and private schools in Sao Paulo, 2017. Socioeconomic status was assessed using a wealth index derived from principal component analysis. Descriptive analyses evaluated differences in total and domain-specific PA by sex, socioeconomic status and maternal education level. OUTCOME MEASURES: We collected data on the frequency and duration that adolescents spent in each PA domain (active transportation, leisure PA and physical education classes) through a self-report questionnaire. RESULTS: On average, adolescents spent 197.7 min/week (95% CI 190.6-204.8) in total PA. The proportion of adolescents achieving at least 60 min/day (≥420 min/week) was 12.7% (95% CI 11.4-14.1), with a higher prevalence in boys (18.3%) and in those with higher socioeconomic status (17.4%). Similar patterns were observed for leisure PA and physical education classes. Active transportation was higher in girls (46.0 min/week; 95% CI 42.6-49.6) than in boys (43.4 min/week, 95% CI 39.9-46.6). Boys and adolescents with higher socioeconomic status and higher maternal education level had higher levels of total PA. CONCLUSIONS: We found a variation in patterns of total and domain-specific PA by sex, socioeconomic status and maternal education level in adolescents from Sao Paulo. Initiatives for promoting PA in adolescents should take these findings into account. © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.